Investigation of appropriate cryoprotectants to be used in the cryopreservation of Thai walking catfish (Clarias macrocephalus) embryo - Wankanapol, A.; Vera Cruz, E. M. (International Journal of Agricultural Technology, 2020)
The appropriate cryoprotectant used in the cryopreservation of Thai walking catfish (Clarias macrocephalus) embryo as investigated. The Thai walking catfish embryo at somites developing stage was exposed to each cryoprotectant solution. The results showed that 40% PG + 5% egg yolk was the least toxic to Thai walking catfish embryo at 40 min exposure time. It was followed by GLY, DMSO and MeOH at 40% + 5% egg yolk, respectively. The permeability is conversely correlated with PG which was the least toxic and had the the lowest permeability while MeOH was the most toxic and highest permeability to Thai walking catfish embryos. Unfortunately, the embryos were not recovery after thawing. The cryoinjuries include ice crystal formation, cold shock and thermal shock might lead to the viability damage.